Analisis SWOT Terhadap Strategi Pengelolaan UKM Pasca Pandemi - Moch. Shohib; Rani Nurul Laili Herzegovina; Achmad Hanafi; Fidhia Yuningtiyas (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2021)
The need on economic influenced some societies either to work or to create new business were part of way to make them in survive. One of them were Lumajang people who had micro, small, medium enterprises that produced crackers. The appearence of Pandemi Covid-19 effected to the business sector so that the accompany must be have new strategic to solve this problems. One of them was UD X as micro, small, medium enterprises which have effected by this pandemi Covid-19. The research was field research, the data collection were interviews, observation, documentation, field-notes, questionnaire, and the direct observation as primary data which supported by secundary data of the research from the texts or other resources by using triangulation analysis. The result of IFASUD analysis that X had some weakness in solving the marketing challenges such as cost of goods expensive and some costs of goods sold. Thus, the result revealed the UD X was quadrant IX showed that UKM Crackers of UD. X has to improve the administration of conglomerate divest, and the quadrant result IV position UD. X should do the aggressive attack in order that the running UKM crackers X could be developed.